Kombinasi Proses Koagulasi dan Aerasi Menggunakan Biji Asam Jawa (Tamarindus Indica) sebagai Biokoagulan pada Limbah Cair Industri Tempe - Nahrawi, Muhammad; Dewi, Ratni; Harunsyah, Harunsyah (Politeknik Negeri Lhokseumawe, 2024)
The impact of the tempe industrial wastewater which has an organic content value if discharged directly into water bodies will endanger the environment. This is due to the large number of pollutant substances present in wastewater, which will cause a decrease in dissolved oxygen levels in wastewater. The purpose of this study was to determine the effect of the dose and timing of tamarind seed bio coagulant on the reduction of chemical oxygen demand (COD), total dissolved solid (TDS), conductivity, turbidity, and pH in tempe industrial wastewater. This research was started by reducing the size of tamarind seeds (brown) so that they became powder, after which they were sieved using an 80 mesh sieve and heated in an oven at 105 ⁰C for 2 hours to reduce the water content. The next process is coagulation and aeration by varying the mass of coagulant 5; 15; 25; 35; and 45 g and time variation of 15; 30; 45; 60; and 75 minutes. Based on the research results, it was found that the water content of tamarind seed powder was 8%, the optimum time and dose were at 75 minutes and 45 g with the percentage of removal of COD, turbidity, TDS, conductivity, and pH each of 97.5%; 61.48%; 19.89%; 16.39%; 3.8. The results of the FTIR characterization of the initial sample obtained a vibrational peak of 3172.90 cm⁻ˡ for the carboxylic acid compound identifying the O-H functional group. And experienced a new vibrational peak after the coagulation and aeration process, namely the alcohol compound identified the vibrational O-H functional group of 3876.92 cm⁻ˡ. From these results, it can be concluded that the tamarind seed bio coagulant can reduce the contaminants in the tempe industrial wastewater.